2016
DOI: 10.3201/eid2208.150696
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing Tool forCyclospora cayetanensis

Abstract: Because the lack of typing tools for Cyclospora cayetanensis has hampered outbreak investigations, we sequenced its genome and developed a genotyping tool. We observed 2 to 10 geographically segregated sequence types at each of 5 selected loci. This new tool could be useful for case linkage and infection/contamination source tracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 4 publications
0
56
1
1
Order By: Relevance
“…Following the generation of C. cayetanensis whole genome assemblies, several studies aimed at the development of typing tools have been published. Guo et al [32] reported the development of a multi-locus sequence typing (MLST) tool based on microsatellite and minisatellite sequences found in the C. cayetanensis genome. A total of 34 isolates with complete sequence data at five loci, formed 25 MLST types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the generation of C. cayetanensis whole genome assemblies, several studies aimed at the development of typing tools have been published. Guo et al [32] reported the development of a multi-locus sequence typing (MLST) tool based on microsatellite and minisatellite sequences found in the C. cayetanensis genome. A total of 34 isolates with complete sequence data at five loci, formed 25 MLST types.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported several challenges such as failure of nested PCR reactions and failure of Sanger sequencing reactions presumably due to mixed C. cayetanensis populations, which may lead to unreadable sequences [32]. Another problem reported by the authors was that the geographical clustering pattern of specimens from the same country at one locus did not confirm to patterns at other loci, presumably because of genetic recombination events [32,33]. In another study, the MLST method was applied to 76 C. cayetanensis-positive samples from China.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genotyping methods for C. cayetanensis have been developed, and successfully used for epidemiological trace-back investigations of cyclosporiasis. Recently, a multilocus sequence typing (MLST) tool involving five microsatellite loci has been established and used for epidemiological source tracking of C. cayetanensis (Guo et al, 2016). There have many other potential uses of this MLST tool .…”
Section: Case-linking and Trackingmentioning
confidence: 99%
“…Nuclear and mitochondrial draft genomes of C. cayetanensis are now available (Qvarnstrom et al, 2015;Guo et al, 2016;Cinar et al, 2015), leading to initial genomic investigations, including MLST analysis (Guo et al, 2016;Hofstetter et al, 2019;Li et al, 2015a). Using genome information and MLST analysis, Guo et al (2016) found variations among C. cayetanensis strains recovered from China, Nepal, Indonesia, Guatemala, Peru, Spain, and the U.S. They found that strains from China grouped well together, whereas types from the U.S. also grouped well together along with types from Peru.…”
Section: Variability Within C Cayetanensismentioning
confidence: 99%